2011
DOI: 10.1111/j.1540-8175.2010.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intima-Media Thickness in Carriers of the LDL-Receptor Defective Gene versus Noncarriers with Newly Detected Asymptomatic Severe Hypercholesterolemia

Abstract: Our data demonstrate that carriers of the LDL-R defective gene have a higher carotid IMT and Apo B/Apo A(1) index than noncarriers, whereas no difference between the groups was found with respect to the level of lipid parameters, ADMA, total homocysteine, cell adhesion molecules and %FMD. Apo-B/A(1) is a predictor of IMT mean in the group of the carriers of the LDL-receptor gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Vladimirova-Kitova et al (150) have found that carriers of a LDL-receptor defective gene have a higher carotid IMT and apo-ratio than non-carriers, whereas no difference between the groups was found with respect to the level of other lipid parameters, ADMA, total homocysteine, cell adhesion molecules, and % flow mediated dilation. Thus the apo-ratio is a predictor of IMT in carriers of this LDL-receptor gene.…”
Section: The Apo-ratio and Relations To Atherosclerosis Vascular Funmentioning
confidence: 99%
See 2 more Smart Citations
“…Vladimirova-Kitova et al (150) have found that carriers of a LDL-receptor defective gene have a higher carotid IMT and apo-ratio than non-carriers, whereas no difference between the groups was found with respect to the level of other lipid parameters, ADMA, total homocysteine, cell adhesion molecules, and % flow mediated dilation. Thus the apo-ratio is a predictor of IMT in carriers of this LDL-receptor gene.…”
Section: The Apo-ratio and Relations To Atherosclerosis Vascular Funmentioning
confidence: 99%
“…In addition, the apo-ratio values are also increased in patients with hypertension, obesity, in pubertal children and in those with heredity for CV diseases (130,141). The apo-ratio is also more closely than lipids related to atherosclerosis in a large number of studies in which different techniques like coronary angiography, arterial wall thickness obtained by ultrasound techniques in the carotid arteries (CIMT values) or even in the coronary arteries by intravascular ultrasound (IVUS) and arterial abnormalities such as the endothelial dysfunction have been used (145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162). Thus, in all these disease or risk situations the aporatio may identify those at an increased risk even better than what is currently performed by using LDL-C or the recently recommended non-HDL-C.…”
Section: Relations To Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies reported that local and systemic arterial stiffness but not IMT are increased in asymptomatic, normotensive hypercholesterolemic children (27). Some studies reported that the type of low‐density lipoprotein (LDL) receptor gene mutation predicts IMT in children with familial hypercholesterolemia (37,38). A mutation in the Apolipoprotein‐B (Apo‐B) gene was associated with a higher carotid IMT (38).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the type of low‐density lipoprotein (LDL) receptor gene mutation predicts IMT in children with familial hypercholesterolemia (37,38). A mutation in the Apolipoprotein‐B (Apo‐B) gene was associated with a higher carotid IMT (38). The Apolipoprotein B/A ratio has been proposed as a predictor of IMT (38,39).…”
Section: Introductionmentioning
confidence: 99%